"

Conditionals and relations in first-order logic

Conditionals and the quantifiers

An important thing we noted in the last chapter was the interplay between the quantifiers and the conditional. The reason quantifiers and the conditional can result in unintuitive consequences is the zeroth-order equivalence between XYX \rightarrow Y and ¬XY\neg X \vee Y, and how pushing and pulling ¬\neg through the quantifiers functions. The following exercise demonstrates some unexpected equivalences in first-order logic regarding the often misleading sentence x(P(x)Q(x))\exists x (P(x) \rightarrow Q(x)), which is neither equivalent to x(P(x)Q(x))\exists x (P(x) \wedge Q(x)), nor to x(P(x)Q(x))\forall x (P(x) \rightarrow Q(x)).

Exercise 8.10. Show that the following facts hold in first-order logic:

  1. x(P(x)Q(x))x(¬P(x)Q(x))\exists x (P(x) \rightarrow Q(x)) \vdash \exists x (\neg P(x) \vee Q(x)) and x(¬P(x)Q(x))x(P(x)Q(x))\exists x (\neg P(x) \vee Q(x)) \vdash \exists x (P(x) \rightarrow Q(x))

  2. x(¬P(x)Q(x))x¬(P(x)¬Q(x))\exists x (\neg P(x) \vee Q(x)) \vdash \exists x \neg (P(x) \wedge \neg Q(x)) and x¬(P(x)¬Q(x))x(¬P(x)Q(x))\exists x \neg (P(x) \wedge \neg Q(x)) \vdash \exists x (\neg P(x) \vee Q(x))

  3. x¬(P(x)¬Q(x))¬x(P(x)¬Q(x))\exists x \neg (P(x) \wedge \neg Q(x)) \vdash \neg \forall x (P(x) \wedge \neg Q(x)) and ¬x(P(x)¬Q(x))x¬(P(x)¬Q(x))\neg \forall x (P(x) \wedge \neg Q(x)) \vdash \exists x \neg (P(x) \wedge \neg Q(x))

  4. x(P(x)Q(x))¬x(P(x)¬Q(x))\exists x (P(x) \rightarrow Q(x)) \vdash \neg \forall x (P(x) \wedge \neg Q(x)) and ¬x(P(x)¬Q(x))x(P(x)Q(x))\neg \forall x (P(x) \wedge \neg Q(x)) \vdash \exists x (P(x) \rightarrow Q(x))

A related problem arises when we think about quantifier placement regarding conditionals. In particular, it should be noted that putting a quantifier in front of a conditional and in the antecedent of a conditional will result in formulas that do not mean the same thing. For example, xy(R(x,y)P(x))\forall x \exists y (R(x, y) \rightarrow P(x)) and x(yR(x,y)P(x))\forall x (\exists y R(x, y) \rightarrow P(x)) mean different things. This is, again, because in some sense, there is a hidden negation in a conditional XYX \rightarrow Y, given its equivalence to ¬XY\neg X \vee Y, and pulling the quantifier over that negation changes it to the other quantifier, by negation pull-through. Accordingly, we can prove the following:

Exercise 8.11. Show that the following facts hold in first-order logic:

  1. xy(R(x,y)P(x))x(yR(x,y)P(x))\forall x \exists y (R(x, y) \rightarrow P(x)) \vdash \forall x (\forall y R(x, y) \rightarrow P(x))

  2. x(yR(x,y)P(x))xy(R(x,y)P(x))\forall x (\forall yR(x, y) \rightarrow P(x)) \vdash \forall x \exists y(R(x, y) \rightarrow P(x))

  3. xy(R(x,y)P(x))x(yR(x,y)P(x))\exists x \forall y (R(x, y) \rightarrow P(x)) \vdash \exists x (\exists y R(x, y) \rightarrow P(x))

  4. x(yR(x,y)P(x))xy(R(x,y)P(x))\exists x (\exists y R(x, y) \rightarrow P(x)) \vdash \exists x \forall y(R(x, y) \rightarrow P(x))

Here is the first one:

image

Properties of relations

Finally, let’s return to properties of relations. We already saw how we can formulate these in first-order logic. In particular:

  1. Reflexivity: xR(x,x)\forall x R(x, x)

  2. Symmetricity: xy(R(x,y)R(y,x))\forall x \forall y (R(x, y) \rightarrow R(y, x))

  3. Transitivity: xyz((R(x,y)R(y,z))R(x,z))\forall x \forall y \forall z ((R(x, y) \wedge R(y, z)) \rightarrow R(x, z))

Using these formulations and first-order logic, we are now able to reason about these properties, and see what they entail.

One obvious thing we can show is that given these general properties, particular instances follow. For example, if reflexivity holds, then for any particular object aa, we have R(a,a)R(a,a). That is, xR(x,x)R(a,a)\forall x R(x,x) \vdash R(a, a) for any aa.

image

We also have that {xy(R(x,y)R(y,x)),R(a,b)}R(b,a)\{\forall x \forall y (R(x, y) \rightarrow R(y, x)), R(a, b)\} \vdash R(b,a).

image

Finally, we also have

{xyz((R(x,y)R(y,z))R(x,z)),R(a,b),R(b,c)R(a,c)}\{\forall x \forall y \forall z ((R(x, y) \wedge R(y, z))\rightarrow R(x, z)), R(a, b), R(b, c) \vdash R(a, c)\}

Exercise 8.12. Show that {xyz((R(x,y)R(y,z))R(x,z)),R(a,b),R(b,c)R(a,c)}\{\forall x \forall y \forall z ((R(x, y) \wedge R(y, z))\rightarrow R(x, z)), R(a, b), R(b, c) \vdash R(a, c)\} holds in first-order logic.

In addition, we can also show some more general facts about relations. For example, if a relation RR is symmetric and transitive, and we know that some object xx relates by RR to some object yy, then from this, it follows that some object relates to itself. That is: {xy(R(x,y)R(y,x)),xyz((R(x,y)R(y,z))R(x,z)),xyR(x,y)}xR(x,x)\{\forall x \forall y (R(x, y) \rightarrow R(y, x)), \forall x \forall y \forall z ((R(x, y) \wedge R(y, z))\rightarrow R(x, z)), \exists x \exists y R(x, y)\} \vdash \exists x R(x,x)

Thankfully, given our tableau system, this is not a particularly hard fact to prove, but it is somewhat tedious. The only trick is to realize that since universal quantifiers can be instantiated with any name independent of one another, the following is an instance of transitivity: (R(a,b)R(b,a))R(a,a)(R(a, b) \wedge R(b, a))\rightarrow R(a, a).

image

Exercise 8.13. If we rearrange the above a bit, we get the following: {xy(R(x,y)R(y,x)),xyz((R(x,y)R(y,z))R(x,z)),¬xR(x,x)}¬xyR(x,y)\begin{aligned} \{\forall x \forall y (R(x, y) \rightarrow R(y, x)), \forall x \forall y \forall z ((R(x, y) \wedge R(y, z))\rightarrow R(x, z)), \neg\exists x R(x, x)\} \\\vdash \neg\exists x \exists y R(x,y) \end{aligned} Show that this holds in first-order logic.

Exercise 8.14. Show that the following holds in first-order logic: {xy(R(x,y)R(y,x)),xyz((R(x,y)R(y,z))R(x,z)),R(a,b),¬R(a,c)}x¬R(x,b)\begin{aligned} \{\forall x \forall y (R(x, y) \rightarrow R(y, x)), \forall x \forall y \forall z ((R(x, y) \wedge R(y, z))\rightarrow R(x, z)), R(a, b), \neg R(a, c)\} \\\vdash \exists x \neg R(x, b) \end{aligned}

This is a hard one! If you can solve this, you have mastered first-order tableau deductions. Here is a hint if you need one. Note that we have Symmetricity, Transitivity, R(a,b)R(a, b) and ¬R(a,c)\neg R(a, c). Moreover, the negation of the conclusion entails that xR(x,b)\forall x R(x, b), so in particular, R(c,b)R(c, b). Now if R(c,b)R(c, b), then by Symmetricity, R(b,c)R(b, c) follows. Then, by Transitivity, R(a,c)R(a, c) follows (given R(a,b)R(a, b)). But ¬R(a,c)\neg R(a, c) is a premise, so we have a contradiction.

License

Icon for the Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License

Learning Logic Backwards Copyright © by Peter Susanszky is licensed under a Creative Commons Attribution-NonCommercial-ShareAlike 4.0 International License, except where otherwise noted.